966. Infectious Diseases among US Resident Student Travelers after Return to the United States: A GeoSentinel Analysis, 2007–2017. (26th November 2018) - Angelo, Kristina M; Haulman, Jean; Terry, Anne; Leung, Daniel; Chen, Lin H; Barnett, Elizabeth; Hagmann, Stefan; Hynes, Noreen; Connor, Bradley; Anderson, Susan; Hamer, Davidson
Abstract: Background: The number of US students studying abroad has more than tripled over the past 20 years. As study abroad programs diversify their destinations, more students are traveling to developing regions, increasing their risk of infectious diseases. Few data exist describing infections acquired by US students while traveling internationally. We describe the spectrum of disease among students who have returned from international travel and suggest how to reduce illness among these travelers. Methods: GeoSentinel is a global network of travel and tropical medicine providers that monitors travel-related morbidity. Records of US resident student travelers, 17–24 years old, who returned to the United States and were given a confirmed travel-related diagnosis at one of 15 US GeoSentinel sites during 2007–2017. Those without ascertainable exposure regions were excluded. Records were analyzed to describe demographic and travel characteristics and diagnoses. Results: There were 432 students included. The median age was 21 years; 69% were female. Over 70% had a pretravel consultation with a healthcare provider. The most common exposure region was sub-Saharan Africa (112 travelers; 26%); the most common exposure countries were India (44 students; 11%), Ecuador (28; 7%), Ghana (25; 6%), and China (24; 6%). Students presented to a GeoSentinel site a median of 8 days (range: 0–181) after travel; 98% were outpatients. The most common diagnosis categories were gastrointestinal (45%) and dermatologic (17%). Of 581 confirmed diagnoses, diarrheal illnesses were most common (165; 28%). Thirty-one (7%) students had a vector-borne disease; 14 (41%) of these were diagnosed with malaria (13 had a pretravel consultation) and 11 (32%) with dengue. Two students were diagnosed with acute HIV. Three had a vaccine-preventable disease (two typhoid; one hepatitis A). Conclusion: Students experienced travel-related infections despite a large proportion receiving pretravel consultations. Students (especially those traveling to a less developed region) should receive specific pretravel instructions (including suggestions for behavioral modification, vaccination, and medication prophylaxis when applicable) to prevent gastrointestinal, vector-borne, sexually transmitted, and vaccine-preventable diseases. Disclosures: All authors: No reported disclosures.